2020
DOI: 10.1021/jacs.0c09588
|View full text |Cite
|
Sign up to set email alerts
|

Monoradicals and Diradicals of Dibenzofluoreno[3,2-b]fluorene Isomers: Mechanisms of Electronic Delocalization

Abstract: The preparation of a series of dibenzo- and tetrabenzo-fused fluoreno­[3,2-b]­fluorenes is disclosed, and the diradicaloid properties of these molecules are compared with those of a similar, previously reported series of anthracene-based diradicaloids. Insights on the diradical mode of delocalization tuning by constitutional isomerism of the external naphthalenes has been explored by means of the physical approach (dissection of the electronic properties in terms of electronic repulsion and transfer integral) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 61 publications
5
45
0
Order By: Relevance
“…39,41,42 Moreover, as shown in Figure 3F, with the increase of temperature, the peaks of H1A and H1B in 1 H-NMR spectra became weaker and broader, which were also often used to verify the presence of diradicals. 39,40 All of these results indicated that 4,6DA1,3BQ seemed to be present in the diradical states.…”
Section: Chemical States Of 46da13bq: Diradicals?mentioning
confidence: 86%
See 1 more Smart Citation
“…39,41,42 Moreover, as shown in Figure 3F, with the increase of temperature, the peaks of H1A and H1B in 1 H-NMR spectra became weaker and broader, which were also often used to verify the presence of diradicals. 39,40 All of these results indicated that 4,6DA1,3BQ seemed to be present in the diradical states.…”
Section: Chemical States Of 46da13bq: Diradicals?mentioning
confidence: 86%
“…The variable-temperature EPR and 1 H-NMR spectroscopy were widely adopted as evidences for the presences of diradicals. [39][40][41][42] We therefore conducted the EPR and 1 H-NMR measurements of 4,6DA1,3BQ at different temperatures. The EPR signal of 4,6DA1,3BQ powders indeed increased with increasing temperature (Figure 3E), which was often regarded as the excited triplet states at elevated temperature.…”
Section: Chemical States Of 46da13bq: Diradicals?mentioning
confidence: 99%
“…For a quinoidal diindenonaphthalene derivative, Haley et al. suggested a higher degree of delocalization of the positive charge compared to that of the negative charge, localized at the fluorenyl position [19] …”
Section: Figurementioning
confidence: 99%
“…For a quinoidal diindenonaphthalene derivative, Haley et al suggested a higher degree of delocalization of the positive charge compared to that of the negative charge, localized at the fluorenyl position. [19] We investigated the reduction of 4 e with potassium anthracenide. The radical anion formed easily; its EPR spectrum is in good agreement with the simulated spectrum (see the Supporting Information).…”
mentioning
confidence: 99%
“…Extending the quinoidal conjugation to make benzothiophene‐fused dicyclopenta[ b , g ]naphthalenes yields indenoindenodibenzothiophene isomers (IIDBTs, 3 – 4 ), [37, 38] as well as a dicyclopenta[ b , i ]anthracene derivative ( 5 ) [39] . These π‐extended systems show significant diradical character that is dramatically increased relative to their carbocyclic analogues [40–42] . Alternating the orientation of the fused benzothiophene (e.g., 3 vs. 4 ) was also determined to be a strategy by which to fine‐tune the effect of the heteroatom by modifying its conjugation in relation to the antiaromatic or diradical motif [38] …”
Section: Introductionmentioning
confidence: 99%